Pemanfaatan Media Pembelajaran Online di SMA Negeri 2 Lais pada Mata Pelajaran Pendidikan Jasmani Olahraga dan Kesehatan - Hudalana, Hudalana; Wardiah, Dessy; Riyoko, Endie (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
The purpose of this study was to determine the use of online learning media at SMA Negeri 2 Laisin the subjects of physical education, sports and health.The type of research and the method usedis a qualitative method. The object in this study is the